FAKTOR-FAKTOR KESULITAN SISWA DALAM MEMBACA TEKS BAHASA ARAB - Wahdah, Yuniarti Amalia (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
This study aims to determine the factors of student difficulties in reading the Arabic text. That's because students often find it difficult to read or understand the content of a text in the Arabic language lessons Muá¹Äla'ah so the impact on learning outcomes Muá¹Äla'ah which is low ie with an average yield of 5.65. Though the ability to read has a very important role in learning Arabic also in everyday life. This research uses descriptive method with qualitative approach. In this study, which is the subject of research is the students of class X MA Darul Arqam Muhammadiyah Garut academic year 2014/2015. Results of the study revealed that factors student difficulties in reading the Arabic text can be classified into two factors. First, internal factors include the ownership experience and language competence of students was low, less interest in reading students, and students' motivation is low. Second, external factors, including factors of teachers who lack the mastery of the material, learning methods that are less attractive, the attitude of the teacher in the learning process assessed to be less enthusiastic, lack of instructional media used, the mobility of the position of a teacher in a classroom that is lacking in monitoring student activities, and lack of availability of textbooks.